Reverse flow injection spectrophotometric method for determination Tenoxicam using 3-Methyl-2-benzothiazolinone hydrazine hydrochloride monohydrate - Allaa Hussein Mhdi (International Journal of Medical Toxicology and Legal Medicine, 2024)
The concentration of tenoxicam (TX) in pure and pharmaceutical tablets was measured by the use of an oxidative coupling reaction in a one-of-a-kind research study that utilised the reverse flow injection method (rFIA). Tenoxicam is used in the process, which entails reacting it with 3-Methyl-2-benzothiazolinone hydrazine hydrochloride monohydrate in the presence of sodium periodate. The end result is the creation of a product that has a green colourpattern.Absorbance was found to be at its maximum at a wavelength of 607 nm, according to the findings.Two to one hundred micrograms per millilitre is the range of concentration linearity that is taken into consideration. A thorough examination of the parameters, which encompasses the concentration of the reagent, the various types of oxidants, the concentrations of the oxidative agents, the flow velocity, the injection volume, and the reaction coil, among other things.